2021
DOI: 10.1088/1752-7163/abd52f
|View full text |Cite
|
Sign up to set email alerts
|

A system for contact free energy expenditure assessment under free-living conditions: monitoring metabolism for weight loss using carbon dioxide emission

Abstract: Weight disorders are strikingly prevalent globally and can contribute to a wide array of potentially fatal diseases spanning from type II diabetes to coronary heart disease. These disorders have a common cause: poor calorie balance. Since energy expenditure (EE) (kcal d−1) constitutes one half of the calorie balance equation (the other half being food intake), its measurement could be of great value to those suffering from weight disorders. A technique for contact free assessment of EE is presented, which only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In this work we focus on assessing λ Acc with high accuracy so that we can formally study the correlation of λ Acc vs. λ o and λ Acc vs. VCO 2 (k gen ). In order to do this, we build upon the previous work [ 26 ] in which λ Acc was assessed using a reference instrument. Here, we build upon that work by using a reference instrument to provide a high-accuracy value of λ Acc (using k gen derived from an FDA 510(k)-cleared device’s VCO 2 measure) and λ 0 from CO 2 decay in the exact same environment following the subject’s departure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work we focus on assessing λ Acc with high accuracy so that we can formally study the correlation of λ Acc vs. λ o and λ Acc vs. VCO 2 (k gen ). In order to do this, we build upon the previous work [ 26 ] in which λ Acc was assessed using a reference instrument. Here, we build upon that work by using a reference instrument to provide a high-accuracy value of λ Acc (using k gen derived from an FDA 510(k)-cleared device’s VCO 2 measure) and λ 0 from CO 2 decay in the exact same environment following the subject’s departure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings [ 26 ] suggested that k gen was correlated to the actual k gen ′ via an environmental correction factor (CF env ) of 1.143, an empirical constant determined to correct for mean error bias originating from any source not accounted for in the “ideal model” used in Equation (1), e.g., imperfect mixing, CO 2 sensor response time, etc., and is used in the model as follows: …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations